Legal Protection of the Welfare of Sports Athletes in the Perspective of Law Number 3 of 2005 - Indra Saputra; Mohamad Tohari (Publikasi Indonesia, 2023)
Sports law in Indonesia has been inadequate, with the absence of comprehensive regulations governing various aspects of national sports. This has resulted in the lack of legal protection and unfulfilled welfare for sports actors who demand their rights. The Sports Law (SKN Law) emphasizes the need to position sports clearly in the national legal system as part of the process and achievement of national development goals. This research adopts a normative approach, using both statutory and conceptual methods. Secondary data serves as the primary source, and qualitative descriptive analysis is employed. Conclusions are drawn deductively, focusing on the topic of Legal Protection for the Welfare of Sports Athletes in relation to Law Number 3 of 2005. The findings reveal that Law Number 3, which established the National Sports System, encompasses interconnected elements such as sports actors, organizations, infrastructure, facilities, community participation, and supporting aspects like science, technology, information, and the sports industry. These elements require support from decision-making institutions, organizational empowerment, human resource development, sports facilities improvement, and adequate funding. The ultimate objective of sporting activities is to ensure the welfare of athletes.